2001
DOI: 10.1002/psc.308
|View full text |Cite
|
Sign up to set email alerts
|

Protein design and folding: template trapping of self‐assembled helical bundles

Abstract: An experimental system is described, permitting a detailed and systematic analysis of the factors governing self-assembly of amphipathic helices, e.g. to a four-helical bundle, a subject of major relevance for tertiary structure formation, protein folding and design. Following the Template Assembled Synthetic Proteins (TASP) approach, helices of different packing potential are competitively assembled in solution with a preformed two-helix TASP molecule, and after equilibration are covalently attached ('templat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Protein de novo design offers a test of our understanding of the factors controlling protein structure, folding and stability. The approach also offers the prospect of access to tailor-made proteins 9 10 11 12 13 14 15 16 17 . One way to overcome the complexity of protein folding is the concept of template-assembled synthetic proteins (TASPs) 18 19 .…”
mentioning
confidence: 99%
“…Protein de novo design offers a test of our understanding of the factors controlling protein structure, folding and stability. The approach also offers the prospect of access to tailor-made proteins 9 10 11 12 13 14 15 16 17 . One way to overcome the complexity of protein folding is the concept of template-assembled synthetic proteins (TASPs) 18 19 .…”
mentioning
confidence: 99%
“…We describe a β-peptide that forms an amphiphilic helix (lipophilic on one side, hydrophilic on the other), and we show that this molecule undergoes self-association in aqueous solution. Pioneering work from DeGrado, Mutter and others has shown that identifying conventional peptides (α-amino acid residues) that form amphiphilic α-helices and self-associate in small clusters constitutes the initial phase in a “hierarchic” design strategy for helix bundle tertiary structure. , Self-associating α-helices have also formed the basis for self- replicating systems , and provided a platform for exploring unusual sources of noncovalent affinity. , Amphiphilic β-peptide helices have found biological applications, 2a-c but controlled self-association has not previously been observed…”
mentioning
confidence: 99%
“…shows the synthetic strategy for the preparation of a fourhelix bundle template-assembled synthetic protein [172][173][174][175]. On the other hand the dual character of the Npys group as an S-protecting and S-activating group [147] has permitted the linkage through disulfide bond between artificial carriers and peptide epitopes [170,176].…”
Section: Chemoselective Ligationmentioning
confidence: 99%